(untitled) (SCIÉNDO INGENIUM, 2021)
The Internet of things interconnects computer objects with the world network, with the help of sensors, applications and communication technology. The devices that are used allow us to obtain information, images, data in real time, improving the ability to transfer information. It covers industries, energy, health, economic and academic sectors, generating metrics for decision-making in different productive sectors. This work evaluates the performance of an application linked to the IoT, which reports improvement in time, cost, facilitating the performance of daily activities of users. The objective of this research is to demonstrate the efficiency of the IoT, through computer applications that carry out different processes according to the needs of people. The app is a very dynamic program aimed at different technologies, such as Android, Iphone, Windows, Mac, Linux, for the connection with the IoT, it can be installed through the network and carry out transactions in a personalized way. The scientific methodology has been used to find results and the agile methodology to integrate the application project with the research. Likewise, it has been possible to understand the relevance of the use of IoT in companies that are rapidly adapting to technological changes.